O27. Gamma camera SPECT calibration for improved quantitative dosimetry. (September 2016) - Moalosi, T.C.G.; Mix, M.; Ellmann, A.; Nolan, L.; Mkhize, T.
Abstract : Introduction: The recent emergence of theranostic pharmaceuticals has made it possible to treat while doing in-vivo dosimetry with a gamma camera. PRRT requires individualized internal dosimetry for every patient because uptake differs across patients. In our department we used to do planar image dosimetry; however this method was prone to errors, because it could not account for overlapping organs and dose underestimation. Quantitative SPECT/CT can mitigate problems encountered in planar image dosimetry by providing a three dimensional image of organs, thereby avoiding overlapping and resulting in more accurate dose estimation. Materials and methods: A 10-ℓ acrylic phantom (NEMA2007/IEC2008) with six fillable spheres was filled with a 177 Lu concentration. The spheres were filled with a higher activity concentration than the background. A SPECT/CT was done on a phantom using a GE Infinia-Hawkeye with clinical acquisition protocol. A 120 projections were acquired using a medium energy general purpose collimator (MEGP) with upper energy peak of 208 keV ± 10%. A low dose CT was used for attenuation correction and the acquired images were reconstructed using an OSEM algorithm using 3 iterations and 15 subsets. A Monte-Carlo-based scatter correction was applied on a workstation from Hermes medical solutions. A cylindrical volume of interest was drawn on the background region, the mean count rate was calculated and the system's volume sensitivity was determined. Results: The volume sensitivity of our gamma camera was determined as 0.535 counts/sec/kBq with STDev: 0.0228, which was then used to determine and compare with known activity concentration in the hot spheres. Under consideration of the known partial volume effect, all spheres showed an accuracy of within 5%. Conclusion: The gamma camera was successfully calibrated and validated for quantitative dosimetry of 177 Lu studies.